THE BISON SAMPLE FROM THE EARLY MIDDLE PLEISTOCENE SITE OF CONTRADA MONTICELLI (APULIA, SOUTHERN ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
Several craniodental and postcranial Bovinae fossil remains coming from the early Middle Pleistocene Contrada Monticelli (CM) site (Castellana Grotte, BA) and preserved at the Museum of Earth Sciences at the University of Bari are here studied in detail for the first time. In addition to Bovinae, the fauna of CM includes several Galerian taxa such as: Canis mosbachensis Soergel, 1925, Palaeoloxodon antiquus (Falconer & Cautley, 1847), Stephanorhinus hundsheimensis Toula, 1902, Equus sp. and Dama cf. roberti Breda & Lister, 2013. Although the scarcity of the sample and the lack of skulls, horncores or metapodial remains should suggest caution, the detailed morphological and biometric analyses allow to refer these remains to a large form of bison, here provisionally classified as Bison cf. schoetensacki Freudenberg, 1914. The presence of this species in the CM site would represent the southernmost occurrence of this taxon in Europe, validating the biochronological attribution of the CM site to the Isernia Faunal Unit (ca. 0.6 Ma). The presence of this bovid, and other large mammals in the site, provides further clues for the reconstruction of the paleoenvironment of Mediterranean Europe during the early Middle Pleistocene.